Attenuation structure in central Anatolia using Belbaşı - Keskin borehole array - Şemin, Korhan Umut. (Thesis (Ph.D.)-Bogazici University. Kandilli Observatory and Earthquake Research Institute, 2018., 2018)
The Multiple Lapse Time Window (MLTW) method has been applied to inves tigate the dominant attenuation mechanism of Central Anatolia region by separating scattering attenuation and intrinsic absorption that are a↵ecting the seismic wave am plitudes. A total of 177 local earthquakes with magnitudes varying between 2.5 – 4.7 and hypocentral distances between 5 to 150 km recorded during 2008-2011 by two borehole type broadband seismometers as well as KOERI seismic stations were se lected according to the criterion deﬁned by SNR > 3 (Signal-to-Noise Ratio). The single station approach of the MLTW allowed us to characterize the lateral variations of attenuation in the region by calculating the attenuation around each station indi vidually for frequencies 1.5, 3, 6, 8, 9 Hz. Moreover, average attenuations were also estimated representing the whole region of Central Anatolia. Final results were com pared with other studies conducted in di↵erent regions around the world. Results of this study show that for frequencies 3 Hz and higher the intrinsic absorption is more prominent than scattering attenuation for the whole of Central Anatolia, especially at south and southeastern parts due to Quaternary volcanism. Comparison of attenuation with di↵erent regions indicates that the Eastern Anatolia has higher attenuation than Central Anatolia whereas Western Anatolia has comparable values of attenuation.
Keywords: Earthquakes -- Belbaşı -- Turkey.; Earthquakes -- Keskin -- Turkey.